Muhammad SAW Sebagai Peletak Dasar Pemerintahan Pluralistis Dalam Islam - Umi Sumbulah (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2008)
Socio-historical setting of Madinah, which was more opened and more cosmo- politan compared to Mecca, was the basic capital for the success of Muhammad in building pluralistic governmental base. The emergence of Madinah consti- tution which involved all Madinah's elements (Muslim and non-Muslim groups) was taken as the tenet of building well-established socio-political system ensuring the equality for all. Considering the admittance of equality, all ele- ments of Madinah held commitment and loyalty toward the prophet leadership. Therefore, they built and created great civilization.